2012
DOI: 10.1080/17441692.2011.594449
|View full text |Cite
|
Sign up to set email alerts
|

A Congolese–US participatory action research partnership to rebuild the lives of rape survivors and their families in eastern Democratic Republic of Congo

Abstract: The Democratic Republic of Congo (DRC) remains an all-too-potent reminder of how war, human rights violations and their related health and economic impacts can devastate a society. The last decade has seen the use of rape as a weapon of war in the DRC, where rebels and soldiers subject women and girls to brutalising attacks, rape, torture and mutilation. Survivors of sexual and gender-based violence (SGBV) are often further traumatised by infections, disease, poverty, stigma and social isolation. Substantial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…Our implementing partner had the expertise and access to engage traditional and administrative village leaders in productive and culturally appropriate economic activities that supported the participation of men and women. 27 Partnerships have the benefit of also building local capacity to provide economic and other development initiatives, which is a critical step to ending a dependence on humanitarian aid and progress to sustainable development that will advance wealth, health and gender equality. It is certain that credit and productive asset transfer programmes alone will not solve the multiple challenges facing families in conflict-affected settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our implementing partner had the expertise and access to engage traditional and administrative village leaders in productive and culturally appropriate economic activities that supported the participation of men and women. 27 Partnerships have the benefit of also building local capacity to provide economic and other development initiatives, which is a critical step to ending a dependence on humanitarian aid and progress to sustainable development that will advance wealth, health and gender equality. It is certain that credit and productive asset transfer programmes alone will not solve the multiple challenges facing families in conflict-affected settings.…”
Section: Discussionmentioning
confidence: 99%
“…13 In 2010, Programme d'Appui aux Initiatives Economiques (PAIDEK), a Congolese microfinance organisation and the Johns Hopkins School of Nursing ( JHSON) joined in collaboration to improve household economic stability, health and safety in rural Eastern DRC. 27 The partners adapted their experience in microcredit, knowledge of productive asset transfer programmes, health and women's empowerment to the DRC context and developed Pigs for Peace (PFP). PFP is a hybrid programme that integrates microcredit and productive asset transfer principles.…”
Section: Key Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] PFP provides a loan to interested and committed households in the form of a 2 to 4 month-old female pig. The PFP microfinance approach uses pigs as a loan because livestock/animals are an important source of economic security and status, similar to a savings account, in rural villages and there are no cultural or religious taboos or gender-based responsibilities related to raising a pig.…”
Section: Methodsmentioning
confidence: 99%
“…Most rural villages in the target area for this study have reported the loss of land and essential tools for farming resulting in limited agricultural productivity. [12], [13] Food insecurity in rural Eastern DRC has been well noted [14][16] [17] specifically that household members typically eat one meal a day and eat the same food every day (e.g., sweet potatoes, corn, cassava) with very limited access to protein from meat, eggs or milk. The looting or loss of animals (e.g.…”
Section: Introductionmentioning
confidence: 99%